Data revisions to German national accounts: Are initial releases good nowcasts? - Till Strohsal; Elias Wolf (Freie Universität Berlin, School of Business & Economics, 2019)
Data revisions to national accounts pose a serious challenge to policy decision making. Well-behaved revisions should be unbiased, small and unpredictable. This paper shows that revisions to German national accounts are biased, large and predictable. Moreover, using filtering techniques designed to process data subject to revisions, the real-time forecasting performance of initial releases can be increased by up to 17%. For total real GDP growth, however, the initial release is an optimal forecast. Yet, given the results for disaggregated variables, the averaging-out of biases and inefficiencies at the aggregate GDP level appears to be good luck rather than good forecasting.
urn:nbn:de:kobv:188-refubium-25147-7
Keywords: C22; C53; C82; E66; 330; Revisions; Real-Time Data; German National Accounts; Nowcasting